Dual doped biocompatible multicolor luminescent carbon dots for bio labeling, UV‐active marker and fluorescent polymer composite. (20th July 2018) - Das, Poushali; Ganguly, Sayan; Mondal, Subhadip; Ghorai, Uttam Kumar; Maity, Priti Prasanna; Choudhary, Sumita; Gangopadhyay, Subhashis; Dhara, Santanu; Banerjee, Susanta; Das, Narayan Ch.
Abstract: We report on metal–non‐metal doped carbon dots with very high photoluminescent properties in solution. Magnesium doping to tamarind extract associated with nitrogen‐doping is for the first time reported here which also produce very high quantum yield. Our aim is to develop such dual doped carbon dots which can also serve living cell imaging with easy permeation towards cells and show non‐cytotoxic attributes. More importantly, the chemical signatures of the carbon dots unveiled in this work can support their easy solubilization into water; even in sub‐ambient temperature. The cytotoxicity assay proves the almost negligible cytotoxic effect against human cell lines. Moreover, the use of carbon dots in UV‐active marker and polymer composites are also performed which gave clear distinguishable features of fluorescent nanoparticles. Hitherto, the carbon dots can be commercially prepared without adopting any rigorous methods and also can be used as non‐photo‐bleachable biomarkers of living cells.